Miqrāʾôt gĕdôlôt hak-keter : mahădûrat yĕsôd ḥădāšā; hohdĕrā maddāʿît ʿal-pî kitĕvê yād ʿattîqîm; wĕ-nilwîm ēlâw: targûmîm ărammiyyîm, ʿal-pî nusḥām šel kitĕvê yād têmāniyyîm mĕduyyāqîm; pērûšîm, mivḥar ʿāšîr šel pērûšîm pĕrî ʿēṭām šel gĕdôlê mĕfārĕšê hap-pĕšāṭ mî-mê-hab-bênnayim ʿal-pî mêṭāv kitĕvê hay-yād hā-ʿattîqîm; ʿên ha-mĕsôrā, bēʾûr û-marʾê-mĕqômôt lĕ-ḵol heʿārôt ha-mĕsôrā šel keter Ăram Ṣôvā. Sefer Yeḥezḳel - Cohen, Menachem; Ben-Asher, Aaron ben Moses, S. X. (Hotsat Universiṭat Bar-Ilan, 2004)
This exceptional new edition of `Mikra`ot Gedolot` is based on the most accurate manuscript - The Aleppo Codex. Among the innovations and improvements incorporated are: Thousands of flaws of the previous and current editions have been corrected. An apparatus called ``Ein Ha-Masorah`` makes the terminology of the Masorah readily comprehensible for the first time. Our edition of the Aramaic targumim and the commentaries is based on a meticulous comparison of the best extant manuscripts. The selection of medieval commentaries in this edition is the most comprehensive of all times. The commentaries have been printed in square characters and are clearly punctuated. All quotations from biblical and rabbinical literature are given their correct references